Reduced ENSO Variability due to a Collapsed Atlantic Meridional Overturning Circulation - Orihuela-Pinto, B; Santoso, A; England, MH; Taschetto, AS; Orihuela Pinto, Luis (Journal of Climate, 2022)
Atlantic meridional overturning circulation (AMOC) collapses have punctuated Earth’s climate in the past, and future projections suggest a weakening and potential collapse in response to global warming and high-latitude ocean freshening. Among its most important teleconnections, the AMOC has been shown to influence El Niño–Southern Oscillation (ENSO), although there is no clear consensus on the tendency of this influence or the mechanisms at play. In this study, we investigate the effect of an AMOC collapse on ENSO by adding freshwater in the North Atlantic in a global climate model. The tropical Pacific mean-state changes caused by the AMOC collapse are found to alter the governing ENSO feedbacks, damping the growth rate of ENSO. As a result, ENSO variability is found to decrease by ∼30% due to weaker air–sea coupling associated with a cooler tropical Pacific and an intensified Walker circulation. The decreased ENSO variability manifests in ∼95% less frequent extreme El Niño events and a shift toward more prevalent central Pacific El Niño than eastern Pacific El Niño events, marked by a reduced ENSO nonlinearity and asymmetry. These results provide mechanistic insights into the possible behavior of past and future ENSO in a scenario of a much weakened or collapsed AMOC.